Genioglossus reflex responses to negative upper airway pressure are altered in people with tetraplegia and obstructive sleep apnoea. (25th April 2018) - Wijesuriya, Nirupama S.; Gainche, Laura; Jordan, Amy S.; Berlowitz, David J.; LeGuen, Mariannick; Rochford, Peter D.; O'Donoghue, Fergal J.; Ruehland, Warren R.; Carberry, Jayne C.; Butler, Jane E.; Eckert, Danny J.
Abstract : Key points: Protective reflexes in the throat area (upper airway) are crucial for breathing. Impairment of these reflexes can cause breathing problems during sleep such as obstructive sleep apnoea (OSA). OSA is very common in people with spinal cord injury for unknown reasons. This study shows major changes in protective reflexes that serve to keep the upper airway open in response to suction pressures in people with tetraplegia and OSA. These results help us understand why OSA is so common in people with tetraplegia and provide new insight into how protective upper airway reflexes work more broadly. Abstract: More than 60% of people with tetraplegia have obstructive sleep apnoea (OSA). However, the specific causes are unknown. Genioglossus, the largest upper‐airway dilator muscle, is important in maintaining upper‐airway patency. Impaired genioglossus muscle function following spinal cord injury may contribute to OSA. This study aimed to determine if genioglossus reflex responses to negative upper‐airway pressure are altered in people with OSA and tetraplegia compared to non‐neurologically impaired able‐bodied individuals with OSA. Genioglossus reflex responses measured via intramuscular electrodes to ∼60 brief (250 ms) pulses of negative upper‐airway pressure (∼−15 cmH2 O at the mask) were compared between 13 participants (2 females) with tetraplegia plus OSA and 9 able‐bodied controls (2 females) matched for age and OSA severity. The initial short‐latency excitatory reflex response was absent in 6/13 people with tetraplegia and 1/9 controls. Genioglossus reflex inhibition in the absence of excitation was observed in three people with tetraplegia and none of the controls. When the excitatory response was present, it was significantly delayed in the tetraplegia group compared to able‐bodied controls: excitation onset latency (mean ± SD) was 32 ± 16  vs . 18 ± 9 ms, P  = 0.045; peak excitation latency was 48 ± 17  vs . 33 ± 8 ms, P  = 0.038. However, when present, amplitude of the excitation response was not different between groups, 195 ± 26  vs . 219 ± 98% at baseline, P  = 0.55. There are major differences in genioglossus reflex morphology and timing in response to rapid changes in airway pressure in people with tetraplegia and OSA. Altered genioglossus function may contribute to the increased risk of OSA in people with tetraplegia. The precise mechanisms mediating these differences are unknown. Key points: Protective reflexes in the throat area (upper airway) are crucial for breathing. Impairment of these reflexes can cause breathing problems during sleep such as obstructive sleep apnoea (OSA). OSA is very common in people with spinal cord injury for unknown reasons. This study shows major changes in protective reflexes that serve to keep the upper airway open in response to suction pressures in people with tetraplegia and OSA. These results help us understand why OSA is so common in people with tetraplegia and provide new insight into how protective upper airway reflexes work more broadly.